An Exploration of Novice Nursing Student’s Experiences of Mentoring in Practice Placement Settings in the United Kingdom - Brand, Darren (International Journal of Practice-based Learning in Health and Social Care, 2020)
TThis study focuses on the experience of new UK student nurses of being mentored in the workplace (placement) setting. There is only limited nursing literature that focuses on the experience of being mentored, whilst there is significant material that examines the role of the mentor. With half of the course being spent in the placement setting, the role of the mentor is pivotal in supporting the student and their learning. Adopting a qualitative design, data was collected through small-group interviews with a cohort of first-year nursing students. Data analysis followed in the form of standard thematic analysis. The Communities of Practice model developed by Lave & Wenger was applied as a theoretical lens. Two main themes emerged from the analysis process: the process of belonging; and that of developing identity as a learner. Whilst there was consensus with the literature in that it was felt that the mentor had a key role to play in supporting and facilitating learning, the participants also felt that the mentor supported them to settle into the team. Further, it was found that until the learner felt part of the wider placement clinical team, the process of learning may be hindered. An argument is presented advocating better preparation of students for learning in the workplace setting as this will enable them to assimilate better the learning offered by mentors and the wider healthcare team.